Permettre la compréhension de l’action dans un jeu d’imitation. Le cas de l’action conjointe entre un artiste chorégraphique et des élèves-danseurs à l’école élémentaire - Virginie Messina (Recherches en Éducation)
The central role played by imitation within the various human societies leads us to consider it from an anthropological point of view. We describe it as a complex process allowing the intergenerational transmission of cultural behaviours and elements. Our didactic approach questions the conditions of progress, that we call an epistemic gain, in teaching-learning situations that are based on imitation. In dance teaching and learning, the transmission of the danced gesture by monstration / reproduction is widely practiced, and is the matter of our study. Under what conditions does imitation enable the construction of new knowledge? In particular, in a teaching-learning situation, what didactic gestures allow those who learn to understand the actions that they have to imitate? To illustrate this, we rely on a situation observed in an elementary school, where a choreographic artist intervenes in a year 4 and 5 class. Based on the Joint Action Theory in Didactics (JATD) and the game model in didactics, our analysis questions imitation as a game of imitation, that is built between the person who teaches the danced gesture (the artist) and those who learn it (pupils-dancers). The observation of this joint action leads us to grasp the conditions that allow students to gradually move from an imitation that retains only the surface features of the gesture shown, to an imitation that shows an understanding of the principles that generate its form.